Method for improving sludge dewatering performance through composite pretreatment
By using high-priced metal salts and transition metal salts to condition the sludge, combined with the control of oxidants, the problems of high cost of Fenton oxidants and complex ultrasonic-acidification-Fenton conditioning process are solved, and the deep dehydration and efficient dehydration performance of the sludge are achieved, simplified Processing process reduces costs and energy consumption.
Patent Information
- Application Number
- CN202411722439.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-10
AI Technical Summary
In the existing sludge dewatering technology, Fenton oxidant has high cost and low efficiency. The ultrasonic-acidification-Fenton continuous conditioning process is complex and has high energy consumption, resulting in poor dehydration effect of sludge and high acid substances used. It is easy to cause secondary pollution.
High-priced metal salts are used to reduce the pH value of sludge, and then the transition metal salts and oxidants are added for conditioning, the amount of oxidant is used to simplify the treatment process, reduce costs and dangers, and polymerize sludge flocs through high-priced cations to reduce the generation of micro-nanocolloids. Improve dehydration performance.
Deep dehydration of the sludge is achieved, the dosage of advanced oxidation reagents is reduced, the treatment process is simplified, the cost and energy consumption is reduced, the dehydration effect is improved, the risk of filter cloth is reduced, and the dosage of agents is significantly reduced. Improved filtration speed and efficiency.
Smart Images

Figure CN119285201A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sludge treatment, and more specifically, relates to a method for improving sludge dewatering performance by composite pretreatment, and the method is particularly suitable for sludge dewatering. Background Art
[0002] Excess sludge comes from the domestic sewage treatment process, and has the characteristics of high water content and high organic matter content. With the development of society, the amount of urban domestic sewage treatment in my country has increased, and the amount of excess sludge has also increased. Because the excess sludge is highly hydrophilic, it is difficult to dehydrate, and it contains a large number of microorganisms and pathogens. If it is not properly disposed of, it will also cause secondary pollution. In recent years, my country has continuously increased its efforts in environmental protection, and the treatment and disposal of sludge has received widespread attention, and the reduction of sludge has become a key research object.
[0003] The output of residual sludge is large and the water content is high, which causes great difficulties in the treatment and utilization of sludge. In order to facilitate subsequent treatment, the sludge is usually pretreated to improve its dewatering performance. At present, the main sludge pretreatment methods are the combination of physical and chemical methods. The sludge conditioning method generally adopted by sewage treatment plants includes the addition of organic or inorganic polymer flocculants for conditioning, followed by dehydration. However, the dehydration effect is general, and the water content is generally around 68% to 75%. Studies have shown that the main reason for the difficulty in sludge dehydration is that the sludge flocs contain a large amount of extracellular polymers (EPS). The sludge EPS carries a large amount of bound water. However, general flocculants cannot destroy EPS and release bound water. Therefore, the sludge cannot be further dehydrated. The Fenton reaction is an advanced oxidation technology with extremely strong oxidizing properties. It can oxidize general organic matter into inorganic states. In recent years, it has been considered to be the most effective conditioning agent for deep sludge dehydration. Fenton reagent can destroy EPS and further release bound water in the sludge, achieving a deep dehydration effect. In addition, the reaction generates Fe 3+ It can reagglomerate sludge particles and enhance sludge dewatering performance. However, the cost of using Fenton's reagent is too high and the efficiency is low.
[0004] In view of the significant improvement of Fenton's oxidizability under low pH conditions, the cost and danger of direct acidification with acid are high. At present, there are many achievements in sludge dehydration. The main patent documents are as follows. In the process published in CN 106746407 A, aeration is performed first, then acidic substances are added, and then Fenton's reagent is added. In the method published in CN 106673383 A, ultrasonic waves are first used to destroy organic matter, then acidification, then Fenton's reagent is used, and finally calcium oxide or calcium hydroxide is added to adjust the pH. In the method published in CN 111362536 A, similar to the above two methods, acid is first used to adjust the sludge pH, then Fenton's reagent is added, and finally cationic polyacrylamide is added. In the above-mentioned conditioning schemes: ① Adding organic acid or inorganic acid to the sludge is costly and difficult to store. Some acids (such as nitric acid, sulfuric acid, etc.) are hazardous chemicals, and improper operation is prone to danger. ② In the above patent, the oxidation intensity is high during the advanced oxidation pretreatment process, and the sludge flocs are non-selectively oxidized and decomposed, resulting in an increase in the content of micro-flocs, which easily blocks the filtration channel of the sludge flocs and affects the sludge dewatering performance. ③ Before pretreatment, the sludge is aerated or ultrasonicated, and alkaline oxides or hydroxides are added after the Fenton reaction to adjust the final pH. The treatment process is complicated, the energy consumption is high, and the reagent cost is also increased. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a method for improving the dewatering performance of sludge by composite pretreatment, wherein the process design of the treatment method is improved, a high-valent metal salt is used to reduce the pH of the sludge, and then a transition metal salt and an oxidant are used for conditioning, and the amount of the oxidant is controlled at the same time, which can overcome the problems of high cost and over-oxidation of Fenton oxidation conditioning alone or ultrasound-acidification-Fenton combined conditioning, and the improvement effect on sludge dewatering performance is better than that of Fenton oxidation conditioning alone; compared with ultrasound-acidification-Fenton combined conditioning, the conditioning process is simple and the cost is low. The method of the present invention can reduce costs and dangers, especially by using high-valent cations to reduce the pH value of the sludge and adjust the pH value of the sludge to 3-5, compared with using acid to adjust the pH value.
[0006] To achieve the above object, the present invention provides a method for improving sludge dewatering performance by composite pretreatment, comprising the following steps:
[0007] (1) firstly adding a high-valent metal salt or a high-valent metal salt polymer to the aqueous sludge to be dehydrated, mixing and stirring, so that the pH value of the system is stabilized at 3 to 5; wherein the high-valent metal salt is a strong acid and weak base salt, and the high-valent metal element contained therein is one or more of trivalent iron, trivalent aluminum, and tetravalent titanium;
[0008] (2) adding a transition metal salt to the system obtained in step (1), and then stirring for 10 to 30 minutes to fully mix the system; wherein the amount of the transition metal salt is 2 to 15% of the dry weight of the aqueous sludge used in step (1); and the transition metal element contained in the transition metal salt is one or more of cobalt, copper, and divalent iron;
[0009] (3) adding an oxidant to the system obtained in step (2), stirring for 10 to 60 minutes to fully mix, and then performing filter pressing and dehydration to obtain a dehydrated mud cake; wherein the amount of the oxidant used is 2 to 30% of the dry weight of the water-containing sludge used in step (1).
[0010] As a further preferred embodiment of the present invention, in step (3), the oxidant is one or more of hydrogen peroxide, calcium peroxide, peracetic acid, peroxymonosulfate, peroxydisulfate, hypochlorous acid, and hypochlorite.
[0011] As a further preferred embodiment of the present invention, in step (3), the oxidant is added in the form of a solid oxidant or an oxidant solution;
[0012] When the oxidant is added in the form of an oxidant solution, the amount of the oxidant used corresponds to the amount of solute oxidant in the oxidant solution.
[0013] As a further preferred embodiment of the present invention, in step (2), the amount of the transition metal salt used is 2 to 15% of the dry weight of the aqueous sludge used in step (1).
[0014] As a further preferred embodiment of the present invention, in step (1), the water content of the water-containing sludge to be dehydrated is 96-99%.
[0015] As a further preferred embodiment of the present invention, in step (1), the pH value of the system is stabilized at 3 to 5, preferably the pH value of the system is stabilized at 5.
[0016] As a further preference of the present invention, the stirring in steps (1) to (3) is performed by mechanical stirring or pipeline mixing.
[0017] Compared with the prior art, the above technical solutions conceived by the present invention can achieve the following
[0018] Beneficial effects:
[0019] 1. The process of the present invention is simple, without complicated pretreatment process and additional high energy consumption process. The present invention does not require aeration or ultrasound of sludge before pretreatment, nor does it require adding alkaline oxides or hydroxides to adjust the final pH after Fenton reaction. The treatment process is simple and the reagent cost is low.
[0020] 2. The pH value of the original water-containing sludge to be dehydrated is generally 6-7. The present invention uses high-valent cations for conditioning (the amount of high-valent metal salt added is aimed at lowering the pH value, specifically adjusting the pH value to 3-5). High-valent cations can be hydrolyzed in the sludge to produce H + , it not only plays the role of hydrolysis and acidification in the system, but also plays the role of coagulation.
[0021] 3. The dosage of the oxidant of the present invention only needs to be 2-30% of the dry weight of the sludge, which greatly reduces the dosage of the advanced oxidizing agent, realizes the moderate oxidation and selective oxidation of the sludge, and can reduce the generation of micro-nano colloids caused by excessive oxidation. In addition, the reduction in the dosage of the agent can also significantly reduce the cost of the agent.
[0022] Compared with the prior art method of using acid to adjust the pH value of the aqueous sludge to be dehydrated, the high-valent metal salts and their polymers used in the present invention are abundant and easy to mine, and with the advancement of technology, the efficiency of the preparation and purification process of metal salts is greatly improved, so they are low-cost and easy to purchase, and can reduce the amount of advanced oxidizing agents added, reduce the generation of micro-nano colloids, and produce flocculation.
[0023] 4. The present invention has good dehydration effect, the moisture content of the dehydrated cake is below 60%, the filter cloth blockage can be reduced during the dehydration process, the dehydration speed in the filtration and filter pressing stages can be increased, and the load on the final disposal can be reduced.
[0024] The high-valent metal salt initially added in the present invention can cause the fine colloids of the sludge to aggregate and agglomerate by compressing the double electric layer and adsorbing and bridging, thereby preventing them from being subsequently oxidized and decomposed into micro-nano colloids. n+ ), which will produce [M(OH)(H2O) m-1 ] (n-1)+ (For detailed reaction mechanism, please see below), [M(OH)(H2O) m-1 ] (n-1)+It can compress the double electric layer of sludge flocs, and through the compression of the double electric layer and the adsorption bridging effect, the fine colloids in the sludge are coagulated and agglomerated, thus preventing them from being subsequently oxidized and decomposed into micro-nano colloids. After high-valent cations are added to the sludge flocs, the adsorption sites on the surface of the sludge flocs can be reduced, and the amount of subsequent transition metals adsorbed on the sludge flocs will be reduced. Previous studies have shown (Water Research, 2019: 148, 60-69) that advanced oxidation sludge conditioning is mainly extracellular oxidation, and free radicals have a very short half-life (such as 10 -9 s), the generation site is only near the transition metal, and the transition metal only exists in the surface layer and liquid phase of the sludge flocs. Therefore, the generation and action area of free radicals are also only in the surface layer and liquid phase of the sludge flocs. The method of the present invention first uses high-valent metal salts and polymers thereof. Since high-valent cations have stronger adsorption capacity than transition metals, they occupy the adsorption sites on the surface of the sludge flocs, resulting in a reduction in the transition metal content on the sludge flocs. Afterwards, an external oxidant is added to react with the transition metal, and the content of active free radicals generated on the surface of the sludge flocs will also be reduced, which will correspondingly reduce the degree of damage to the sludge flocs, thereby reducing the generation of micro-nano flocs and achieving a moderate oxidation effect.
[0025] In the prior art, the agents generally used for sludge conditioning are either coagulants (such as metals with high-valent cations, Fe / Al, etc.), or oxidants are directly used to condition the sludge, such as Fenton's reagent or persulfate oxidation, etc.; among them, the ability of using a coagulant alone to improve the sludge dewatering performance is limited, and it can only compress the double electrical layer of the sludge, and will not reduce the particle size of the sludge flocs, so that the bound water inside the sludge flocs cannot be released; the oxidation system using only Fenton or ferrous persulfate activation will produce a large number of active free radicals, which will reduce the overall particle size of the sludge flocs (the particle size of flocs with large, medium and small particle sizes will all be reduced), which will lead to the generation of a large number of micro-colloids, which will clog the filter cloth during the sludge dewatering process. If only the amount of Fenton or ferrous persulfate activation is reduced, the sludge conditioning effect is very poor (as verified by the examples in Comparative Examples 3 and 4 below). At the same time, the pH of the aqueous sludge system to be dehydrated is relatively high (close to 7), and the transition metal (such as divalent iron) is in a hydroxyferrous state, not a divalent iron ion, and cannot react with hydrogen peroxide to generate active free radicals and trivalent iron, so the dehydration performance cannot be improved (as verified by the example of Comparative Example 8 below). The present invention can have two effects by first adding a high-valent metal salt or a high-valent metal salt polymer (such as trivalent iron), one is to reduce the initial pH of the sludge, and the other is to occupy part of the binding sites of the sludge flocs, which can greatly reduce the subsequent dosage of the advanced oxidation reagent (the dosage is only 40% of the amount of the advanced oxidation reagent). The price of the oxidant is very high, such as the price of hydrogen peroxide is more than 2,000 yuan / ton (the price comes from the purchase order of a water plant in Xi'an, data in December 2023; the same below), and the price of persulfate is 5,000 yuan / ton. The price of liquid polyferric sulfate is only 500 yuan / ton, and the initial addition of liquid polyferric sulfate is only used to adjust the pH value to 3-5, and the addition amount does not exceed 40% of the dry mass of the sludge. In addition, due to the reduction in the amount of oxidant added, the oxidizing property is reduced, the amount of micro-colloids produced is greatly reduced, and the clogging of the filter cloth is alleviated. Therefore, the highlights of the present invention are: a. Let the high-valent metal salt (or high-valent metal salt polymer) reduce the pH of the sludge; b. The high-valent metal salt (or high-valent metal salt polymer) occupies some adsorption sites in the sludge.
[0026] At the same time, in order to ensure that the transition metal combines with the oxidant and reacts on the sludge, the method of the present invention adopts the following measures:
[0027] a. The requirements for the degree of stirring and mixing are relatively high. After adding a high-valent metal salt (or a high-valent metal salt polymer) to the aqueous sludge in the first step of the method of the present invention to mix and stir to adjust the pH value, after adding the transition metal salt in the second step, it is necessary to fully stir and mix to ensure that it is fully in contact with the sludge and fully adsorbed by the sludge. Moreover, after adding the oxidant in the third step, it is necessary to stir for 10 to 60 minutes to fully mix and ensure that the transition metal adsorbed by the sludge is in full contact with the oxidant. Because the organic content in the sludge is high, the oxidant reacts quickly in the sludge and has a short survival time. Uneven stirring and mixing will cause the oxidant to be consumed by the organic matter in the sludge or the oxidant to react with self-generated oxidizing substances, and it will not contact the sludge surface and react with the transition metal.
[0028] b. In the first step of the method of the present invention, when adding high-valent metal salt (or high-valent metal salt polymer) to the aqueous sludge and mixing and stirring to adjust the pH value, the target pH value requirement can be preferably selected as 5. This is because: since high-valent metal salts and transition metals compete for adsorption sites in the sludge, the addition of high-valent metal salts should be reduced as much as possible under the premise of ensuring pH, so as to free up more adsorption sites in the sludge and indirectly improve the utilization efficiency of the oxidant.
[0029] c. In the first step of the method of the present invention, a high-valent metal salt (or a high-valent metal salt polymer) is added to the aqueous sludge to mix and stir to adjust the pH value to 3 to 5; when a transition metal salt is added in the second step, the amount of the transition metal salt is 2 to 15% of the dry weight of the aqueous sludge, so that the amount of the high-valent metal and the transition metal is strictly controlled. This is because: due to the limited adsorption sites in the sludge, too many metal ions will exist in the sewage in a free state, which will consume the oxidant and reduce the utilization rate of the oxidant.
[0030] In the method of the present invention, in the first step, a high-valent metal salt (or a high-valent metal salt polymer) is added to the aqueous sludge to mix and stir to adjust the pH value, in the second step, a transition metal salt is added, and in the third step, an oxidant is added. In this way, the order of adding the reagents is strictly controlled to ensure that the dewatering performance of the sludge is improved. For example, after adding a small amount of high-valent cationic coagulant, adding only an oxidant (such as hydrogen peroxide or persulfate) is ineffective (as verified by the example of Comparative Example 5 below).
[0031] Moreover, under the reagent dosing sequence of the method of the present invention, the subsequent dosage of the advanced oxidant can be reduced to 40% of the normal dosage, achieving a similar deep dehydration effect, while reducing the clogging of the filter cloth and the frequency of filter cloth washing. The overall processing cost can be reduced to 50% of the normal Fenton reagent conditioning cost.
[0032] In summary, the composite pretreatment method of the present invention can reduce the dosage of advanced oxidizing agents, achieve moderate oxidation of sludge, and reduce the generation of micro-nano colloids caused by excessive oxidation; it can reduce filter cloth blockage during the dehydration process and increase the dehydration speed in the filtration and filter pressing stages. Reducing the dosage of agents can also significantly reduce the cost of agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the composite pretreatment conditioning process of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0035] The composite pretreatment method of the present invention improves the dewatering performance of sludge, firstly adding high-valent metal salt to adjust the initial pH of sludge to 3-5, the high-valent metal salt can be trivalent iron salt, trivalent aluminum salt, etc., then adding advanced oxidation reagent to condition the sludge, the advanced oxidation reagent can be transition metal catalyzed hydrogen peroxide, persulfate, hypochlorite, etc., and then dewatering the conditioned sludge.
[0036] Combination Figure 1 The main reaction mechanism of the method of the present invention is as follows:
[0037] S01; high-valent metal salt (M n+ ) Conditioning:
[0038] M n+ +nH2O→nH + +M(OH)n
[0039] [M(H2O) m ] n+ →[M(OH)(H2O) m-1 ] (n-1)+ +H +
[0040] S02 and S03; Advanced oxidation conditioning, where R n+ It is a transition metal, and H2O2 is a typical external oxidant. Transition metal catalytic oxidants can produce oxidizing substances such as OH, which can degrade sludge organic matter (YH) and destroy the sludge floc structure.
[0041] R n+ +H2O2→·OH+R (n+1)+ +OH-
[0042] R (n+1)+ +H2O2→R n+ +H + +HO2
[0043] R n+ +·OH→R (n+1)+ +OH -
[0044] H2O2+·OH→R (n+1)+ +OH -
[0045] R n+ +HO2·→R (n+1)+ +HO2 -
[0046] R (n+1)+ +HO2·→R n+ +H + +O2
[0047] YH+·OH→Y·+H2O
[0048] Y·+O2→YO2·
[0049] Y·+H2O2→YOH+·OH
[0050] Y·+R n+ →Y - +R (n+1)+
[0051] Y·+R (n+1)+ →Y + +R n+
[0052] S04; Sludge dewatering: plate and frame filter press dewatering.
[0053] The following are specific embodiments:
[0054] Example 1: Take concentrated sludge with a water content of 97.87%, an organic matter content of 63.22%, and a pH of 6.3. Use iron sulfate (added in solid form) to acidify the sludge to pH = 4.5 and keep it stable (after the high-valent metal salt and sludge are mixed and stirred, the pH change is less than 0.05 / min, that is, the pH value is considered to remain stable; the same below), then add 8% cobalt sulfate (added in solid form) based on the dry sludge, stir for 10 minutes, mix thoroughly, then add 12% sodium persulfate (added in solid form) based on the dry sludge, stir for 30 minutes, mix thoroughly to react, and filter press to dehydrate after complete reaction. The moisture content of the mud cake was measured to be 59.72%, the capillary water absorption (CST) was 11.4s, and the sludge specific resistance (SRF) was reduced to 1.12×10 12 m·kg -1 .
[0055] Example 2: Take the concentrated sludge, the moisture content is 98.23%, the organic matter content is 58.87%, and the pH is 6.5. Use ferric chloride (added in solid form) to acidify the sludge to pH = 3.5 and keep it stable, then add ferrous chloride (added in solid form) at 8% of the sludge dry basis, stir for 15 minutes, mix thoroughly, then add sodium hypochlorite at 15% of the sludge dry basis (it can be in solution or solid form, as long as the mass of the solute sodium hypochlorite or solid sodium hypochlorite accounts for 15% of the sludge dry basis), stir for 30 minutes to mix thoroughly and react, and filter press to dehydrate after complete reaction. The moisture content of the mud cake was measured to be 59.73%, the capillary water absorption (CST) was 10.2s and the sludge specific resistance (SRF) was reduced to 0.96×10 12 m·kg -1 .
[0056] Example 3: Take concentrated sludge with a water content of 98.05%, an organic matter content of 58.49% and a pH of 6.3. Use aluminum chloride (added in solid form) to acidify the sludge to pH = 5 and keep it stable, then add cobalt chloride (added in solid form) at 10% of the sludge dry basis and stir for 15 minutes to mix thoroughly, then add hydrogen peroxide at 15% of the sludge dry basis (added in the form of a 10% hydrogen peroxide solution, the mass of solute in the hydrogen peroxide solution ÷ the mass of sludge dry basis × 100% = 15%), stir for 40 minutes to mix thoroughly to react, and filter press to dehydrate after complete reaction. The moisture content of the mud cake was measured to be 60.61%, the capillary water absorption (CST) was 11.9s and the sludge specific resistance (SRF) was reduced to 1.13×10 12 m·kg -1 .
[0057] Example 4: Take the concentrated sludge, the moisture content is 98.05%, the organic matter content is 59.04%, and the pH is 6.8. Use aluminum ferric sulfate (added in solid form) to acidify the sludge to pH = 4 and keep it stable, then add 6% ferrous sulfate (added in solid form) of the sludge dry basis, stir for 30 minutes to mix thoroughly, then add 12% calcium peroxide (added in solid form) of the sludge dry basis, stir for 40 minutes to mix thoroughly to react, and filter press dehydration after complete reaction. The measured moisture content of the mud cake is 58.35%, the capillary water absorption (CST) is 9.8s and the sludge specific resistance (SRF) is reduced to 0.92×10 12 m·kg -1 .
[0058] Example 5: Take the concentrated sludge, the moisture content is 97.58%, the organic matter content is 61.27%, and the pH is 6.8. Use polyferric sulfate (liquid addition, wherein the iron content is 5%) to acidify the sludge to pH = 5 and keep it stable (polyferric sulfate accounts for about 20% of the dry sludge), then add ferrous sulfate (solid addition) at 10% of the dry sludge basis and stir for 30 minutes, mix thoroughly, then add hydrogen peroxide at 12% of the dry sludge basis (add in the form of a 10% hydrogen peroxide solution, the solute mass in the hydrogen peroxide solution ÷ the dry sludge mass × 100% = 12%), stir for 40 minutes to mix thoroughly and react, and filter press to dehydrate after complete reaction. The moisture content of the mud cake was measured to be 57.83%, the capillary water absorption (CST) was 8.7s and the sludge specific resistance (SRF) was reduced to 0.83×10 12 m·kg -1 .
[0059] Cost accounting (calculated based on 1 ton of absolutely dry sludge):
[0060] Polyferric sulfate: unit price 500 yuan / ton, dosage 20% of sludge dry basis, i.e. 0.20×500 yuan / ton=100 yuan / ton;
[0061] Ferrous sulfate: unit price is 300 yuan / ton, and the dosage is 10% of the dry basis of sludge, that is, 0.1×300 yuan / ton=30 yuan / ton;
[0062] Hydrogen peroxide: unit price is 2,000 yuan / ton, concentration is 30%. Dosage is 12% of dry sludge, i.e. 0.12÷0.3×2,000 yuan / ton=800 yuan / ton. The total cost of treating one ton of absolutely dry sludge is 930 yuan.
[0063] Example 6
[0064] Take the concentrated sludge, the moisture content is 97.58%, the organic matter content is 61.27%, and the pH is 6.5. Use ferric sulfate (added in solid form) to acidify the sludge to pH = 5 and keep it stable, then add ferrous sulfate (added in solid form) at 10% of the sludge dry basis, stir for 30 minutes, mix thoroughly, then add hydrogen peroxide at 12% of the sludge dry basis (added in the form of a 10% hydrogen peroxide solution, the solute mass in the hydrogen peroxide solution ÷ the sludge dry basis mass × 100% = 12%), stir for 50 minutes to mix thoroughly for reaction, and filter press dehydration after complete reaction. The moisture content of the mud cake was measured to be 57.83%, the capillary water absorption (CST) was 8.7s and the sludge specific resistance (SRF) was reduced to 0.83×10 12 m·kg -1 .
[0065] Example 7
[0066] Take the concentrated sludge, the moisture content is 97.58%, the organic matter content is 61.27%, and the pH is 6.7. Use ferric chloride (added in solid form) to acidify the sludge to pH = 5 and keep it stable, then add 15% ferrous chloride (added in solid form) based on the dry basis of the sludge, stir for 30 minutes, mix thoroughly, then add 15% hydrogen peroxide based on the dry basis of the sludge (added in the form of a 10% hydrogen peroxide solution, the solute mass in the hydrogen peroxide solution ÷ the dry basis mass of the sludge × 100% = 15%), stir for 60 minutes to mix thoroughly for reaction, and filter press dehydration after complete reaction. The moisture content of the mud cake was measured to be 55.73%, the capillary water absorption (CST) was 12.4s and the sludge specific resistance (SRF) was reduced to 0.96×10 12 m·kg -1 .
[0067] Comparative Example 1
[0068] Take the concentrated sludge, the moisture content is 97.48%, the organic matter content is 64.27%, and the pH is 6.8. Use dilute nitric acid (added in liquid form, concentration is 10%) to acidify the sludge to pH = 3 and keep it stable, then add 5% ferrous sulfate (added in solid form) on the dry basis of the sludge, stir for 10 minutes, mix thoroughly, then add 10% hydrogen peroxide on the dry basis of the sludge (added in the form of a 10% hydrogen peroxide solution, the solute mass in the hydrogen peroxide solution ÷ the dry basis mass of the sludge × 100% = 10%), stir for 20 minutes to fully mix and react, and filter press to dehydrate after complete reaction. The moisture content of the mud cake was measured to be 64.07%.
[0069] Reason for failure: Nitric acid will oxidize the transition metal (ferrous sulfate).
[0070] Comparative Example 2
[0071] Take the concentrated sludge, the moisture content is 98.21%, the organic matter content is 62.57%, and the pH is 7.1. Use oxalic acid (added in liquid form, concentration is 30%) to acidify the sludge to pH = 3 and keep it stable, then add 5% ferrous sulfate (added in solid form) of the sludge dry basis and stir for 10 minutes, mix thoroughly, then add 10% hydrogen peroxide of the sludge dry basis (added in the form of 10% hydrogen peroxide solution, the solute mass in the hydrogen peroxide solution ÷ the sludge dry basis mass × 100% = 10%), stir for 20 minutes to fully mix and react, and filter press to dehydrate after complete reaction. The moisture content of the mud cake was measured to be 63.68%.
[0072] Cause of failure: Oxalic acid will be oxidized by the oxidant (hydrogen peroxide).
[0073] Comparative Example 3
[0074] Take the concentrated sludge, the moisture content is 99.32%, the organic matter content is 57.77%, and the pH is 7.0. Use ferric chloride (added in solid form) to acidify the sludge to pH = 3 and keep it stable, then add 1% ferrous chloride (added in solid form) on a dry basis of the sludge, stir for 30 minutes, mix thoroughly, then add 15% hydrogen peroxide on a dry basis of the sludge (added in the form of a 10% hydrogen peroxide solution, the solute mass in the hydrogen peroxide solution ÷ the dry basis mass of the sludge × 100% = 15%), stir for 40 minutes to fully mix and react, and filter press to dehydrate after complete reaction. The moisture content of the mud cake was measured to be 63.77%.
[0075] Cause of failure: Insufficient amount of transition metal (ferrous chloride) added.
[0076] Comparative Example 4
[0077] Take the concentrated sludge, the moisture content is 98.49%, the organic matter content is 61.64%, and the pH is 6.8. Use polyferric sulfate (liquid addition, in which the iron content is 5%) to acidify the sludge to pH = 3 (polyferric sulfate accounts for about 30% of the dry basis of the sludge) and keep it stable, then add 10% of ferrous sulfate (solid addition) to the dry basis of the sludge, stir for 20 minutes, mix thoroughly, then add 1% of hydrogen peroxide to the dry basis of the sludge (add in the form of a 10% hydrogen peroxide solution, the solute mass in the hydrogen peroxide solution ÷ the dry basis mass of the sludge × 100% = 1%), stir for 10 minutes to fully mix and react, and filter press dehydration after complete reaction. The moisture content of the mud cake was measured to be 66.48%.
[0078] Cause of failure: Insufficient dosage of oxidant (hydrogen peroxide).
[0079] Comparative Example 5
[0080] Take the concentrated sludge, the moisture content is 97.21%, the organic matter content is 60.74%, and the pH is 6.4. Use polyferric sulfate (liquid addition, the iron content is 5%) to acidify the sludge to pH = 3 (polyferric sulfate accounts for about 30% of the dry sludge) and keep it stable, then add 10% hydrogen peroxide to the dry sludge (add in the form of 10% hydrogen peroxide solution, the solute mass in the hydrogen peroxide solution ÷ the dry sludge mass × 100% = 10%), stir for 30 minutes to fully mix and react, and filter and dehydrate after complete reaction. The moisture content of the mud cake is measured to be 66.53%.
[0081] Reason for failure: No transition metals including divalent cobalt, monovalent copper and divalent iron were added.
[0082] Comparative Example 6
[0083] Take the concentrated sludge, the moisture content is 97.21%, the organic matter content is 60.74%, and the pH is 6.8. Add 60% polyferric sulfate (liquid addition, the iron content is 5%) to the sludge dry basis, stir for 30 minutes to fully mix and react, and filter press and dehydrate after complete reaction. The moisture content of the mud cake is measured to be 66.38%. Increasing the amount of polyferric sulfate will not reduce the moisture content of the sludge.
[0084] Cause of failure: Using coagulant alone has limited effect on reducing the moisture content of sludge.
[0085] Comparative Example 7
[0086] Take the concentrated sludge, the moisture content is 97.21%, the organic matter content is 60.74%, and the pH is 6.8. Add 15% polyaluminium chloride on the dry basis of the sludge (add in the form of a 10% polyaluminium chloride solution, the solute mass in the polyaluminium chloride solution ÷ the dry basis mass of the sludge × 100% = 15%; and the content of aluminum in the polyaluminium chloride is 30%), stir for 30 minutes to fully mix and react, and filter press to dehydrate after complete reaction. The moisture content of the mud cake is measured to be 67.23%. Increasing the amount of polyaluminium chloride will not reduce the moisture content of the sludge.
[0087] Cause of failure: Using coagulant alone has limited effect on reducing the moisture content of sludge.
[0088] Comparative Example 8
[0089] Take the concentrated sludge, the moisture content is 98.56%, the organic matter content is 59.23%, and the pH is 7.3. Add 15% ferrous sulfate (solid addition) to the sludge dry basis, stir for 30 minutes, mix thoroughly, then add 25% hydrogen peroxide (add in the form of 10% hydrogen peroxide solution, the solute mass in the hydrogen peroxide solution ÷ the sludge dry basis mass × 100% = 25%) to the sludge dry basis, stir for 60 minutes to mix thoroughly for reaction, and filter press dehydration after complete reaction. The moisture content of the mud cake is measured to be 62.23%. However, there are problems such as the sludge particles are too fine after conditioning, which causes the filter plate and filter cloth to be blocked, resulting in a decrease in production.
[0090] Cause of failure: Using Fenton reagent alone for conditioning greatly reduces the particle size of sludge flocs, blocking the sludge deep dehydration channel.
[0091] Cost accounting - calculated based on 1 ton of absolutely dry sludge:
[0092] Ferrous sulfate: unit price is 300 yuan / ton, and the dosage is 15% of the dry basis of sludge, i.e. 0.15×300 yuan / ton=45 yuan / ton;
[0093] Hydrogen peroxide: unit price is 2,000 yuan / ton, concentration is 30%. Dosage is 25% of dry sludge, i.e. 0.25÷0.3×2,000 yuan / ton=1,667 yuan / ton. The total cost of treating one ton of absolutely dry sludge is 1,711 yuan.
[0094] The processing cost increased by nearly 1 times compared with Example 5.
[0095] Unless otherwise specified, the percentages (eg, water content, dosage ratio, concentration of reagent solution, etc.) appearing in the present invention are all percentages by mass.
[0096] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving sludge dewatering performance by composite pretreatment, characterized in that: The steps include: (1) firstly adding a high-valent metal salt or a high-valent metal salt polymer to the aqueous sludge to be dehydrated, mixing and stirring, so that the pH value of the system is stabilized at 3 to 5; wherein the high-valent metal salt is a strong acid and weak base salt, and the high-valent metal element contained therein is one or more of trivalent iron, trivalent aluminum, and tetravalent titanium; (2) adding a transition metal salt to the system obtained in step (1), and then stirring for 10 to 30 minutes to fully mix the system; wherein the amount of the transition metal salt is 2 to 15% of the dry weight of the aqueous sludge used in step (1); and the transition metal element contained in the transition metal salt is one or more of a divalent cobalt element, a monovalent copper element, and a divalent iron element; (3) adding an oxidant to the system obtained in step (2), stirring for 10 to 60 minutes to fully mix, and then performing filter pressing and dehydration to obtain a dehydrated mud cake; wherein the amount of the oxidant used is 2 to 30% of the dry weight of the water-containing sludge used in step (1).
2. The method for improving sludge dewatering performance by composite pretreatment according to claim 1, characterized in that: In step (3), the oxidant is one or more of hydrogen peroxide, calcium peroxide, peracetic acid, peroxymonosulfate, peroxydisulfate, hypochlorous acid, and hypochlorite.
3. The method for improving sludge dewatering performance by composite pretreatment according to claim 1, characterized in that: In step (3), the oxidant is added in the form of a solid oxidant or an oxidant solution; When the oxidant is added in the form of an oxidant solution, the amount of the oxidant used corresponds to the amount of solute oxidant in the oxidant solution.
4. The method for improving sludge dewatering performance by composite pretreatment as claimed in claim 1, characterized in that: In step (2), the amount of the transition metal salt used is 2 to 15% of the dry weight of the aqueous sludge used in step (1).
5. The method for improving sludge dewatering performance by composite pretreatment according to claim 1, characterized in that: In step (1), the water content of the water-containing sludge to be dehydrated is 96-99%.
6. The method for improving sludge dewatering performance by composite pretreatment according to claim 1, characterized in that: In step (1), the pH value of the system is stabilized at 3 to 5, preferably at 5.
7. The method for improving sludge dewatering performance by composite pretreatment according to claim 1, characterized in that: The stirring in steps (1) to (3) is performed by mechanical stirring or pipeline mixing.
Citation Information
Patent Citations
Method for strengthening dehydration of petrochemical residual sludge based on physical and chemical combined pretreatment
CN106673383A
Technology for improving dewaterability of excess sludge
CN106746407A
Application of Fenton-flocculation combined conditioning method in dehydration of municipal domestic sludge
CN111362536A
Sludge deep dehydration method
CN103319066A
Deep dewatering method for municipal sludge
CN105693065A
Cited By
Harmless treatment process for bottom mud of rivers and lakes
CN120025057A
A harmless treatment process for river and lake bottom sludge
CN120025057B
A method for improving sludge dewatering performance while promoting sludge disinfection
CN120573913B